The importance of beta diversity in local gall-inducing arthropod distribution - Medianero,Enrique (2010)
Many studies over the past twenty years have documented the richness of arthropod galling species around the world, and some have proposed hypotheses to explain local and global patterns of galling species richness. However, few studies have been directed toward understanding how the gall-inducing species are locally distributed. The aim of this study was to determine the distribution of gall-inducing arthropods species at Coiba National Park, a tropical habitat on the Pacific coast of Panama. Our results suggest that more gall-inducing species had an aggregated distribution, and gall-inducing arthropod diversity shows a strong beta diversity component. Geographic distance was not correlated with similarity in gall-inducing species composition between the studied sites. This fact has important implications when trying to estimate gall-inducing arthropod richness and general patterns, and could cause contradictory results for hypotheses that attempt to explain the local and global patterns of galling species richness.